Diagnostic Findings of Transmissible Viral Proventriculitis Associated with Chicken Proventricular Necrosis Virus in Processed Broiler Chickens in Argentina - Carlos Daniel Gornatti-Churria; Natàlia Majó; Melissa Macías-Rioseco; Rosa M. Valle; Patricio A. García; Carmen F. Jerry (Viruses)
Transmissible viral proventriculitis (TVP) and chicken proventricular necrosis virus (CPNV) affect the broiler industry globally and are emerging diseases of economic importance. Here, we present the findings of TVP from processed broiler carcasses in Argentina following marked condemnation at the processing plant. We studied a total of 122 abnormally presenting proventriculi at processing from 42-to-50-day-old, male Cobb500™ broiler chicken carcasses from 11 farms belonging to the same company in 13 episodes of proventriculi–gizzards condemnation between December 2021 and April 2022. The proventriculi were enlarged and pale with a widened gastric isthmus. A histopathologic lesion score system was developed based on the presence of a combination of key microscopic findings, the distribution, and the severity of the lesions. Scoring of the affected proventriculi revealed 65% (79/122) with a score of 4, 23% (28/122) with a score of 3, and 12% (15/122) with a score of 2. Focal to multifocal immunoreactivity against the VP2-CPNV antigen within the necrotic glandular epithelial cells was noted in the affected proventriculi using immunohistochemistry. We found 84.4% (103/122) of the studied proventriculi with TVP lesions grossly and microscopically scored were positive for CPNV by RT-PCR. The sequencing results of the PCR product showed a high nucleotide sequence similarity (88.97%) to previously published VP1-CPNV sequences. We confirmed CPNV infection in most of the TVP affected proventriculi in all condemnation episodes at a broiler chicken processing plant in Argentina during the studied period. This study documents TVP associated with CPNV detection at processing plants in Argentina for the first time.